2020
DOI: 10.1016/s2214-109x(20)30044-9
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of two household survey modules for measuring stillbirths and neonatal deaths in five countries: the Every Newborn-INDEPTH study

Abstract: Background An estimated 5·1 million stillbirths and neonatal deaths occur annually. Household surveys, most notably the Demographic and Health Survey (DHS), run in more than 90 countries and are the main data source from the highest burden regions, but data-quality concerns remain. We aimed to compare two questionnaires: a full birth history module with additional questions on pregnancy losses (FBH+; the current DHS standard) and a full pregnancy history module (FPH), which collects information on all livebirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…For stillbirths, we applied a simple test comparing the SBR to NMR ratio by survey modules, but this is simplistic and any potential variation with the level of NMR and SBR in LMICs is as yet poorly understood [7,18]. SBR were lower than expected in almost all the surveys conducted by DHS phase, including both FBH and FPH, and this was consistent with findings from the EN-INDEPTH study [42].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…For stillbirths, we applied a simple test comparing the SBR to NMR ratio by survey modules, but this is simplistic and any potential variation with the level of NMR and SBR in LMICs is as yet poorly understood [7,18]. SBR were lower than expected in almost all the surveys conducted by DHS phase, including both FBH and FPH, and this was consistent with findings from the EN-INDEPTH study [42].…”
Section: Discussionsupporting
confidence: 64%
“…The change followed findings from the EN-INDEPTH study, a randomised comparison of the DHS-VII model questionnaire's FBH plus additional questions on recent non-live births to the most recent FPH implemented in Nepal. Evidence from that study suggested that FPH improved reporting of stillbirths, but had no effect for neonatal deaths [42]. However, whilst the FPH approach resulted in higher SBR estimates overall, this finding varied across sites underlining that changes to the questionnaire tools may be necessary but not sufficient, with other factors such as survey training and implementation likely playing an important role.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study also investigated the performance of existing and/or modified survey questions regarding other pregnancy-related outcomes, and conducted qualitative research exploring barriers and enablers to reporting these outcomes (Additional file 2). Further details have been published in the protocol and main study paper [19,20]. The survey questions were administered face-to-face, and data were collected on tablets using the Survey Solutions system [21].…”
Section: En-indepth Study Design and Settingsmentioning
confidence: 99%
“…In 2019, an estimated 11 million pregnant women were infected by Plasmodium in sub-Saharan Africa, where P. falciparum is the most prevalent parasite species, accounting for 99.7% of estimated malaria cases ( 1 ). P. falciparum infection contracted during pregnancy can lead to placental malaria (PM), a condition that could cause very serious clinical outcomes for both mother and child, including maternal anemia ( 2 , 3 ), hypertension ( 4 , 5 ), stillbirth ( 6 , 7 ) as well as low birth-weight infants, which affected over 800,000 children in 2019 ( 1 ).…”
Section: Introductionmentioning
confidence: 99%